2023
DOI: 10.1039/d3ra01550e
|View full text |Cite
|
Sign up to set email alerts
|

Advanced progress on the significant influences of multi-dimensional nanofillers on the tribological performance of coatings

Ruili Wang,
Yahui Xiong,
Kang Yang
et al.

Abstract: The typical nanofillers, involving 0D nanofillers, 1D nanofillers , 2D nanofillers, and 3D nanofillers for friction reduction and anti-wear of metal/ceramic/polymer matrix composite coatings are shown in the picture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 254 publications
(368 reference statements)
0
4
0
Order By: Relevance
“…As a result, the adhesive qualities of the surface were shown to increase even more. It is feasible to develop oxygen-rich nanofilms on PEEK with a high surface energy, which can result in an increased cell performance [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the adhesive qualities of the surface were shown to increase even more. It is feasible to develop oxygen-rich nanofilms on PEEK with a high surface energy, which can result in an increased cell performance [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…1 Here, modifying the ETT surface through coatings can be an interesting approach that might present a solution to these problems. [2][3][4][5] Indeed, coatings generated from different materials have already been used to modify the surfaces of many devices such as medical equipment and improved important properties including the tribological performance, 3,[6][7][8] anti-biofouling behavior, 9,10 biocompatibility, 11 and hemocompatibility. 12 In recent work, we introduced a setup that enabled us to perform ex vivo extubation tests on porcine tracheas, and we employed this setup to assess the functionality of mucin coatings generated on endotracheal tubes (ETTs).…”
Section: Introductionmentioning
confidence: 99%
“…1 Here, modifying the ETT surface through coatings can be an interesting approach that might present a solution to these problems. 2–5 Indeed, coatings generated from different materials have already been used to modify the surfaces of many devices such as medical equipment and improved important properties including the tribological performance, 3,6–8 anti-biofouling behavior, 9,10 biocompatibility, 11 and hemocompatibility. 12…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al found that thinner CFRPs exhibit increased susceptibility to damage during relative sliding, whereas thicker CFRPs have higher resistance to ploughing, which impacts the friction and wear characteristics [7]. Solid lubrication coatings that can withstand high-temperature, high-pressure, and high-vacuum conditions, can enhance the hardness and wear resistance of the base material, thereby extending the lifespan of CFRP and reducing frictional losses in CFRP components [8,9].…”
Section: Introductionmentioning
confidence: 99%